Exercise logic.propositional.dnf.unicode

Description
Proposition to DNF (unicode support)

Derivation

Final term is not finished
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬((r ↔ s) ∨ ¬s) ∧ ¬¬((F ∨ q) → p))
logic.propositional.notnot
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬((r ↔ s) ∨ ¬s) ∧ ((F ∨ q) → p))
logic.propositional.falsezeroor
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬((r ↔ s) ∨ ¬s) ∧ (q → p))
logic.propositional.demorganor
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬(r ↔ s) ∧ ¬¬s ∧ (q → p))
logic.propositional.notnot
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬(r ↔ s) ∧ s ∧ (q → p))
logic.propositional.defimpl
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬(r ↔ s) ∧ s ∧ (¬q ∨ p))
logic.propositional.defequiv
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬((r ∧ s) ∨ (¬r ∧ ¬s)) ∧ s ∧ (¬q ∨ p))
logic.propositional.demorganor
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬(r ∧ s) ∧ ¬(¬r ∧ ¬s) ∧ s ∧ (¬q ∨ p))
logic.propositional.demorganand
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬(r ∧ s) ∧ (¬¬r ∨ ¬¬s) ∧ s ∧ (¬q ∨ p))
logic.propositional.notnot
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬(r ∧ s) ∧ (r ∨ ¬¬s) ∧ s ∧ (¬q ∨ p))
logic.propositional.notnot
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬(r ∧ s) ∧ (r ∨ s) ∧ s ∧ (¬q ∨ p))
logic.propositional.absorpand
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬(r ∧ s) ∧ s ∧ (¬q ∨ p))
logic.propositional.demorganand
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ ((¬r ∨ ¬s) ∧ s ∧ (¬q ∨ p))
logic.propositional.andoveror
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ ((¬r ∨ ¬s) ∧ ((s ∧ ¬q) ∨ (s ∧ p)))
logic.propositional.andoveror
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ ((¬r ∨ ¬s) ∧ s ∧ ¬q) ∨ ((¬r ∨ ¬s) ∧ s ∧ p)
logic.propositional.andoveror
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬r ∧ s ∧ ¬q) ∨ (¬s ∧ s ∧ ¬q) ∨ ((¬r ∨ ¬s) ∧ s ∧ p)
logic.propositional.andoveror
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬r ∧ s ∧ ¬q) ∨ (¬s ∧ s ∧ ¬q) ∨ (¬r ∧ s ∧ p) ∨ (¬s ∧ s ∧ p)
logic.propositional.compland
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬r ∧ s ∧ ¬q) ∨ (F ∧ ¬q) ∨ (¬r ∧ s ∧ p) ∨ (¬s ∧ s ∧ p)
logic.propositional.compland
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬r ∧ s ∧ ¬q) ∨ (F ∧ ¬q) ∨ (¬r ∧ s ∧ p) ∨ (F ∧ p)
logic.propositional.falsezeroand
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬r ∧ s ∧ ¬q) ∨ F ∨ (¬r ∧ s ∧ p) ∨ (F ∧ p)
logic.propositional.falsezeroand
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬r ∧ s ∧ ¬q) ∨ F ∨ (¬r ∧ s ∧ p) ∨ F
logic.propositional.falsezeroor
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬r ∧ s ∧ ¬q) ∨ (¬r ∧ s ∧ p) ∨ F
logic.propositional.falsezeroor
(¬(q → p) ∧ ((r ↔ s) ∨ ¬s)) ∨ (¬r ∧ s ∧ ¬q) ∨ (¬r ∧ s ∧ p)